Penyebaran Dakwah Gus Baha' Melalui Media Sosial Pada Lingkungan Mahasiswa UIN Salatiga - Kristina; Aoli Nur Faoziya, Zakiya; Rifa’i, Achmad; Ilham Maulana, Risnaldi (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2023)
This research aims to describe the spread of Gus Baha''s preaching through social media within the UIN Salatiga student environment. The method used in this research is descriptive qualitative research using the interview method analysis type of research. This method is used by researchers to describe or analyze the existence of the spread of Gus Baha's preaching in the UIN Salatiga environment. This research was conducted on UIN Salatiga students with a total of 20 students. The results of this research show that many UIN Salatiga students do not know about Gus Baha's preaching. By using the interview method in this research, students enthusiastically answered questions about Gus Baha'. The results obtained from this research, UIN Salatiga students expressed their opinions such as agreeing, disagreeing, and disagreeing with Gus Baha''s preaching. Based on observations, this research considers various aspects and looks at the final results of observations regarding the spread of Gus Baha's preaching on social media, especially in the UIN Salatiga student environment, some students do not know Gus Baha'. The impact of this research is that students only ignore Gus Baha''s preaching that appears on their social media and some students only watch the video of Gus Baha''s preaching without paying attention to the content of the preaching message conveyed.